Trained Circulating Monocytes in Atherosclerosis: Ex Vivo Model Approach - Nikiforov, Nikita G.; Wetzker, Reinhard; Kubekina, Marina V.; Petukhova, Anna V.; Kirichenko, Tatiana V.; Orekhov, Alexander N. (Frontiers in Pharmacology, 2019)
Inflammation is one of the key processes in the pathogenesis of atherosclerosis. Numerous studies are focused on the local inflammatory processes associated with atherosclerotic plaque initiation and progression. However, changes in the activation state of circulating monocytes, the main components of the innate immunity, may precede the local events. In this article, we discuss tolerance, which results in decreased ability of monocytes to be activated by pathogens and other stimuli, and training, the ability of monocyte to potentiate the response to pathological stimuli, and their relation to atherosclerosis. We also present previously unpublished results of the experiments that our group performed with monocytes / macrophages isolated from atherosclerosis patients. Our data allow assuming the existence of relationship between the formation of monocyte training and the degree of atherosclerosis progression. The suppression of trained immunity ex-vivo seems to be a perspective model for searching anti-atherogenic drugs.